Clinical efficacy analysis of partial cystectomy and radical cystectomy in the treatment of muscle-invasive sarcomatoid carcinoma of the urinary bladder - Xiao, Jiansheng; Chen, Hua; Ge, Jiaqi; Liu, Tairong (Frontiers in Oncology, 2024)
Objective This study compares the clinical efficacy of partial cystectomy (PC) versus radical cystectomy (RC) in the treatment of muscle-invasive bladder urothelial carcinoma (SCUB) through a retrospective analysis. Methods We retrospectively analyzed the clinical data of 20 patients diagnosed with muscle-invasive SCUB from July 2015 to August 2023 at Ganzhou People’s Hospital. All patients underwent surgical treatment followed by chemotherapy, with 9 receiving PC and 11 undergoing RC. We compared the average survival time of deceased patients for both treatments and conducted survival and multivariate analyses using the Kaplan-Meier method and Cox proportional hazards model, respectively. Results All 20 patients were postoperatively diagnosed with muscle-invasive SCUB and were followed up for 4 to 60 months. The average survival time for patients undergoing PC was 11.5 months, with survival rates at 1 year, 2 years, and 5 years of 55.56%, 22.22%, and 11.11%, respectively. In contrast, patients receiving RC had an extended average survival time of 22.5 months, and their 1-year, 2-year, and 5-year survival rates increased to 63.64%, 36.36%, and 18.18%, respectively. Survival analysis revealed statistically significant differences in prognosis between PC and RC for the treatment of muscle-invasive SCUB (P<0.05). Conclusion SCUB is a rare malignant tumor with unique biological characteristics often associated with poor prognosis. Upon diagnosis, RC should be considered as an early treatment approach when the patient’s overall condition permits.